Exploring the concept of Measurement at the foundational stage: A hands-on journey through experiential learning - Sridevi, K.V.; Sharma, Purnima (SCHOOL SCIENCE, 2025)
In school education, it is crucial that the learning is both meaningful and enjoyable for students. Various theoretical frameworks have also supported that learning is maximum when it integrates with learner’s experiences, ideas, interaction, reflection and internationalisation of concepts so that they can be applied in their daily lives. It is where experiential learning gains recognition as one of the most effective pedagogical approaches as it involves enquiry, hands-on activities, group work and the didactic approach. This paper explores using experiential learning as a part of pedagogy in the field of mathematics for the foundational stage. It offers the teacher or teacher trainees an illustration in the form of a lesson plan explaining different activities and learning aids that can be used in a classroom. This illustration is a culmination of pedagogical ideas, experiences and research(es) related to Kolb’s cycle of experiential learning used in the Indian context. The paper also provides the teacher the autonomy and space to create and mold the experiential learning activities according to their resources characterised by cultural, geographical, linguistic and social disparities.